The United Nations - Bailey, Sydney D. author. aut Link
VII, 176 p.
Keywords: The book serves as a comprehensive yet concise guide to the political workings of the United Nations system. It details the purposes and structure of the Organisation, with specific chapters on peace and security, disarmament, and human rights. In the final chapter the problems facing the UN are examined. Tables provide information on the size and distribution of UN membership, peacekeeping operations and the use of the Security Council veto. It includes the full text of the UN Charter.